Effects of friction stir processing on wear properties of WC–12%Co sprayed on 52100 steel. (5th December 2015) - Rahbar-kelishami, A.; Abdollah-zadeh, A.; Hadavi, M.M.; Banerji, A.; Alpas, A.; Gerlich, A.P.
Abstract: A WC–12%Co coating was thermally sprayed on a 52100 steel substrate and subsequently friction stir processing (FSP) was performed on this layer. The wear resistance and hardness was compared before and after FSP. Optical and SEM revealed that FSP intermixes the sprayed layer with the substrate, reduces porosity, and enhances both hardness and wear performances. 3D profilometry mapping was conducted to evaluate the wear track depth and its morphology. Refined grain structures and a martensitic structure with retained austenite are promoted by the FSP treatment. This leads to formation of new intermetallic and carbides which were detected by X-ray diffraction, thus accounting for the increased hardness and improved wear resistance. Graphical abstract: Highlights: Performing FSP on a WC coating sprayed on 52100 steel improved the wear resistance. FSP transformed the α + Fe3 C structure to a martensitic one with retained austenite. This transformation can lead to an increase of both hardness and toughness. Breaking down the WC particles produces a dense structure with higher hardness. This higher wear resistance can be attributed to a new phase formation induced by FSP.